2010
DOI: 10.1088/0004-637x/718/2/1158
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Wet, Dry, and Mixed Galaxy Mergers Occur? A Study of the Environments of Close Galaxy Pairs in the Deep2 Galaxy Redshift Survey

Abstract: We study the environment of wet, dry, and mixed galaxy mergers at 0.75 < z < 1.2 using close pairs in the DEEP2 Galaxy Redshift Survey, aiming to establish a clear picture of how the cosmic evolution of various merger types relate to the observed large-scale extra-galactic environment and its role in the growth of redsequence galaxies. We find that the typical environment of mixed and dry mergers is denser than that of wet mergers, mostly due to the color-density relation. While the galaxy companion rate (N c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
128
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 105 publications
24
128
0
2
Order By: Relevance
“…The T MM from Kitzbichler & White (2008) are typically longer than others in the literature (e.g., Patton & Atfield 2008;Lin et al 2010) or similar to those from N-body/hydrodynamical simulations (Lotz et al 2010b,a). Thus, we expect, if anything, a shorter T MM , which implies a larger number density of ETGs due to mergers.…”
Section: Uncertainties In the Modelmentioning
confidence: 59%
See 1 more Smart Citation
“…The T MM from Kitzbichler & White (2008) are typically longer than others in the literature (e.g., Patton & Atfield 2008;Lin et al 2010) or similar to those from N-body/hydrodynamical simulations (Lotz et al 2010b,a). Thus, we expect, if anything, a shorter T MM , which implies a larger number density of ETGs due to mergers.…”
Section: Uncertainties In the Modelmentioning
confidence: 59%
“…We measured the median-weighted stellar mass from MASSIV sources in each of the three redshift bins under study, and estimated the merger time scale for these stellar masses. These time scales already include the factor C m (see Patton & Atfield 2008;Bundy et al 2009;Lin et al 2010;López-Sanjuan et al 2011), so we take C m = 1 in the following. In addition, López-Sanjuan et al (2011) show that the time scales Table 2.…”
Section: The Gas-rich Major Merger Rate In Massivmentioning
confidence: 99%
“…On the other hand, different authors (e.g. Kauffmann et al 2004;Baldry et al 2006;Cooper et al 2006;Skibba et al 2009;Lin et al 2010;Patton et al 2011) show that paired galaxies are found in higher density environments than their control sample and that interacting galaxies are redder before the interaction starts, owing to the older stellar population present in higher density environments. However, pairs and isolated galaxies in our samples are selected from equal density environments i.e.…”
Section: Colors and Stellar Populationmentioning
confidence: 96%
“…Similar results were found by Ellison et al (2010), who analyzed the dependence of interactions on cluster-centric distance, finding that for close pairs the fraction of asymmetric galaxies (associated with tidal disruptions) is highest in the cluster centers. Moreover, Lin et al (2010) showed that the galaxy pair fraction increases with density. We also study the luminosity galaxy ranking in pairs within groups (Fig.…”
Section: Luminosity Galaxy Ranking and Pair Distribution In Groupsmentioning
confidence: 99%
“…Mergers with composite colors in the elliptical region are classified as dry mergers, while mergers with combined colors in the starburst region are considered as wet mergers, and those objects with merged colors in the Sbc/Scd regions are regarded as mix mergers. It should be noted that our classifications are on the basis of blurred-together colors of both components of a merging system (e.g., luminosity-weighted combined colors), which is different from the original definition of "gas-rich wet mergers" or "gas-poor dry mergers" (e.g., Lin et al 2010). For comparison, we show an example of mergers of PS1 r -and y -band, CFHT r -band, and SDSS r -band in Fig.…”
Section: Preliminary Classification and Stellar Massmentioning
confidence: 80%